Імперативи духовності в контексті суспільства знань - Дудченко, В. (Культура народов Причерноморья, 2013)
Досліджується розвиток та становлення дискурсу суспільства знань, його евристичний
потенціал та технічні можливості в перспективі цивілізаційного поступу людства. Аналізуються
духовно-етичні імперативи в техногенному розвитку сучасного інформаційного суспільства. Исследуется развитие и становление дискурса общества знаний, его эвристический
потенциал и технические возможности в перспективе цивилизационного развития человечества.
Анализируются духовно-этические императивы в техногенном развитии современного
информационного общества. We investigate the formation and development of the knowledge society discourse, its heuristic
capacity and technical capabilities in the future civilization of mankind. Examines the spiritual and ethical
imperatives in anthropogenic development of modern information society.
Solved modern studies that write about approaching a new era - Age Spirituality, Rights and Education as
priority material side of civilization has access to its spiritual component (D. Likhachev). In particular,
according to V. Andrushchenko, modern civilization has gradually transformed into a new stage of development
– noosphere civilization. An important feature of this transition is to build a knowledge society and a huge
increase in the role of spiritual values and imperatives as major factors of social progress.
It is shown that inclusion of Ukraine into the world educational space, the Bologna process necessitate
restructuring of education and training on spiritual principles. That spirit should be the basis of education, and
education - to promote, exposure and development of the spiritual potential of the individual.
It is emphasized that the transition of humanity to spiritual ideals due to socio-cultural evolution of mankind, its
occurrence in the era of global mode of existence. At this stage, the international community came to realize
himself not only as a part of nature, social relations, or culture, but as a product of universal space integrity of the dominant spiritual core on which is built the livelihoods of individuals, formed the historical destiny of the
nation.